The impact of the digital divide on synchronous online teaching in Kazakhstan during COVID-19 school closures - Amirova, Aida; Nurumov, Kaidar; Kasa, Rita; Akhmetzhanova, Aida; Kuzekova, Aizhan (Frontiers in Education, 2023)
This paper examines how factors associated with the digital divide such as ICT access, digital skills, and outcomes influenced synchronous online teaching in urban and rural schools in Kazakhstan during COVID-19 school closures. In addition to school location, this paper addresses how the speed and steadiness of the internet connection, and teacher characteristics such as age, qualification, and experience influenced teacher usage of synchronous teaching and learning mediums. Data in this paper consists of a nationally representative sample of nearly 4 000 teachers. This study found that the digital divide narrows when schools provide teachers with ICT access. While both, the speed of the internet and rural-urban residency have statistically significant effects on the use of ICT tools by teachers when considered separately, the interaction term between these two covariates was not statistically significant. Results indicated that age, experience, teacher workload and professional qualification were important determinants in teachers' ability to engage in synchronous teaching.